Nanotechnology-based non-viral vectors for gene delivery in cardiovascular diseases - Jiao, Liping; Sun, Zhuokai; Sun, Zhihong; Liu, Jie; Deng, Guanjun; Wang, Xiaozhong (Frontiers in Bioengineering and Biotechnology, 2024)
Gene therapy is a technique that rectifies defective or abnormal genes by introducing exogenous genes into target cells to cure the disease. Although gene therapy has gained some accomplishment for the diagnosis and therapy of inherited or acquired cardiovascular diseases, how to efficiently and specifically deliver targeted genes to the lesion sites without being cleared by the blood system remains challenging. Based on nanotechnology development, the non-viral vectors provide a promising strategy for overcoming the difficulties in gene therapy. At present, according to the physicochemical properties, nanotechnology-based non-viral vectors include polymers, liposomes, lipid nanoparticles, and inorganic nanoparticles. Non-viral vectors have an advantage in safety, efficiency, and easy production, possessing potential clinical application value when compared with viral vectors. Therefore, we summarized recent research progress of gene therapy for cardiovascular diseases based on commonly used non-viral vectors, hopefully providing guidance and orientation for future relevant research.